Crowdsourcing to promote hepatitis C testing and linkage-to-care in China: a randomized controlled trial protocol - William C. W. Wong; Nancy S. Yang; Jingjing Li; Hang Li; Eric Y. F. Wan; Thomas Fitzpatrick; Yuan Xiong; Wai-Kay Seto; Polin Chan; Ruihong Liu; Weiming Tang; Joseph D. Tucker (BMC, 2020)
Abstract Background Hepatitis C virus (HCV) is a growing public health problem with a large disease burden worldwide. In China many people living with HCV are unaware of their hepatitis status and not connected to care and treatment. Crowdsourcing is a technique that invites the public to create health promotion materials and has been found to increase HIV testing uptake, including in China. This trial aims to evaluate crowdsourcing as a strategy to improve HCV awareness, testing and linkage-to-care in China. Methods A randomized controlled, two-armed trial (RCT) is being conducted in Shenzhen with 1006 participants recruited from primary care sectors of The University of Hong Kong-Shenzhen Hospital. Eligible participants are ≥30 years old; a resident in Shenzhen for at least one month after recruitment; no screening for HCV within the past 12 months and not known to have chronic HCV; and, having a WeChat social media account. Allocation is 1:1. Both groups will be administered a baseline and a follow-up survey (4-week post-enrollment). The intervention group will receive crowdsourcing materials to promote HCV testing once a week for two weeks and feedback will be collected thereafter, while the control group will receive no promotional materials. Feedback collected will be judged by a panel and selected to be implemented to improve the intervention continuously. Those identified positive for HCV antibodies will be referred to gastroenterologists for confirmation and treatment. The primary outcome will be confirmed HCV testing uptake, and secondary outcomes include HCV confirmatory testing and initiation of HCV treatment with follow-ups with specialist providers. Data will be collected on Survey Star@ via mobile devices. Discussion This will be the first study to evaluate the impact of crowdsourcing to improve viral hepatitis testing and linkage-to-care in the health facilities. This RCT will contribute to the existing literature on interventions to improve viral hepatitis testing in primary care setting, and inform future strategies to improve HCV care training for primary care providers in China. Trial registration Chinese Clinical Trial Registry. ChiCTR1900025771. Registered September 7th, 2019, http://www.chictr.org.cn/showprojen.aspx?proj=42788